PENENTUAN JENIS TUMBUHAN PENCIRI PADA EMPAT KOMUNITAS TUMBUHAN DI KAWASAN KARST MAROS-PANGKEP SULAWESI SELATAN - Amran Ahmad; Dariana Nurdin (PERENNIAL, 2007)
The study aims to determine the distinguishing plant species within a plant community forest in the karst area of Maros-Pangkep. Plots of 20 meters by 20 meters were purposively established on 40 different locations representing proportionally facies of massif, porous, leyered and metamorphosed carbonate rocks. Tree dimensions in terms of height and diameter of trees in every plot were measured. The data were examinated through table method and principal component analysis (PCA). The study indicated that the distiguishing plant species determined by table method, only could diffrenciate between the group of communities over massif, porous rock facies and the group of communities over layered, metamorphosed rock facies. Whereas, determining plant species characteristic by PCA method gave sharper interpretation about the distiguishing plant species of plant communities among massif, porous, layered and matamorphosed rock facies. Keywords: Karst area, South Sulawesi